Answer:
fourth degree monomial
Step-by-step explanation:
This is the answer by definition.
∠A ≅ ∠T . . . . given
AX ≅ TX . . . . given
∠AXM ≅ ∠TXH . . . . vertical angles are congruent
ΔAXM ≅ ΔTXH . . . . ASA theorem
MX ≅ HX . . . . CPCTC
___
The acronyms that invoke theorems based on two or three sides being congruent are inapplicable in this case.
SSS
SAS
━━━━━━━☆☆━━━━━━━
▹ Answer
1 - 9/7n
▹ Step-by-Step Explanation
1/7 - 3(3/7n - 2/7)
Remove the parentheses (Distribute -3 among the parentheses):
1/7 - 9/7n + 6/7
Calculate:
1 - 9/7n
Hope this helps!
CloutAnswers ❁
━━━━━━━☆☆━━━━━━━
Answer:
1-9/7n
Step-by-step explanation:
Answer:
Yes it seems that it is right
Answer:
x=4
Step-by-step explanation:
hope it will help
First no.=x
2nd no.=2x
3rd no. =2x+6
x+2x+2x+6=26
5x+6=26
5×=26-6
5x =20.......divide both sides by 5
x=4
1st no.=x=4
The equation of circle C will be;
⇒ (x + 5)² + (y - 2)² = 7.61²
The circle is a closed two dimensional figure , in which the set of all points is equidistance from the center.
Given that;
The points j(-8,9) and k(-2,-5) are endpoints of a diameter of circle C.
Now,
Since, The points j(-8,9) and k(-2,-5) are endpoints of a diameter of circle C.
Hence, The diameter of circle = √(- 2 - (-8))² + (- 5 - 9)²
= √ 6² + 14²
= √36 + 196
= √232
= 15.23
Thus, The radius of circle = 15.23 / 2
= 7.61
And, The center of the circle = (- 8 + (-2)) / 2 , (9 + (-5))/2
= (- 5, 2)
So, The equation circle C is,
⇒ (x - (-5))² + (y - 2)² = 7.61²
⇒ (x + 5)² + (y - 2)² = 7.61²
Learn more about the circle visit:
#SPJ5
Answer:
(x+5)² + (y-2)² =58
Step-by-step explanation:
"Your answer needs to be at least 20 characters long"
"For every movie there is a pair of students in our class who have both seen it." Hint: Use three quantifiers - one for the movie and two for a pair of students.
b. Negate the quantified proposition you wrote for part (a) (i.e., place a "¬" in front of it). Use de Morganâs law for quantifiers to move the negation inside the quantifiers.
c. Translate you answer for part (b) back to plain English.
Answer:
Step-by-step explanation:
a) Recall the quantifiers .
Then, we can translate the proposition as follows
b) Recall that an expression of the form its negation is of the form which means that it is not true that for all elements the proposition P holds. Equivalently, we have that the negation of an expression of the form is which means that there is at least one x such that P doesn't hold. Using this, we get the following
By De Morgan's law, we have that
So, the final statement is
c)
This statement means: There is a movie that for every pair of students, at least one of the students hasn't seen the movie yet.
The quantified proposition expresses that for every movie, there is a pair of students who have both seen it. The negated proposition states that there exists a movie that no pair of students have both seen.
a. The English sentence can be expressed as the quantified proposition: ∀m ∈ M, ∃ (s1, s2) ∈ D^2, S(s1,m) ∧ S(s2,m)
b. The negation of the quantified proposition is: ∃m ∈ M, ∀(s1, s2) ∈ D^2, ¬(S(s1,m) ∧ S(s2,m))
c. The translation of the negated proposition is: There exists a movie that no pair of students in our class have both seen.
#SPJ3